Lessons learned from recent destructive Van, Turkey earthquakes - Yon, Burak; Sayin, Erkut; Calayir, Yusuf; Ulucan, Zulfu Cinar; Karatas, Mehmet; Sahin, Humeyra; Bildik, Abdullah Tevfik (Techno-Press, 2015)
A destructive earthquake, the magnitude of this earthquake was 7.2, hit Van, Turkey on October 23, 2011. After this devastating earthquake, a moderate earthquake which had 5.7 magnitude on November 9, 2011 occurred in Edremit, Van. These earthquakes caused heavy damages and collapses in many reinforced concrete buildings with loss of lives. In this paper, characteristics of ground motions of these earthquakes were studied and, deficiencies in structural elements and engineering faults such as poor workmanship and quality of construction, soft and weak stories, strong beam-weak column, short column, large overhang, hammering and unconfined gable wall were investigated. According to the observations, it was seen that, low quality of structural materials, lack of engineering services, inappropriate design and construction with insufficient detailing of the structural elements were the main reasons of heavy damages.
Keywords: 2011 Van earthquakes; ground motion characteristics; reinforced concrete buildings; earthquake damages